Chapter 2 Artists, producers, and managers Anatomy of a relationship - Rodrigues, Vânia (Taylor & Francis, 2024)
This volume takes stock of the ways in which the regimes of artistic creation and production intersect, lending special attention to emergent discourses and work models of producing and managing theatre, dance, and performance – through the lenses of creative producers. This book suggests that social protection failures, longstanding institutional shortcomings, and the dilemmas of social and environmental sustainability are pushing arts management and production modi operandi towards a review of its expansionist assumptions and managerial hyper-productivist processes. By documenting singular ‘counter-management’ experiences in Portugal, Belgium, France, and Brazil, this study makes a strong claim for a reassessment of the role of producers and art managers as reflective practitioners and as pivotal elements towards more sustainable artistic practices. This study will be of great interest to students and scholars in theatre and performance studies, policymakers, and cultural professionals.